Draft Ninth Five Year Plan (1997-2002) and Annual Plan (1997-98) Part I - Plan in Outline - Analysis of Sectoral Outlay and Statistical Statements Government of Goa - Planning Commission (Planning Commission, 1997)
In comparison to the rest of the country, the living standard in the territory was generally better. Per capita income was the twice the per capita income of the Indian Union. Per capita consumption was also higher and so also average yield per hectare of rice. Health and Education were also better than rest of the country. Since, most of the States in the Indian Union were under developed,- this comparison was not an indicator of developmental standards of the territory.
Government of Goa, Directorate of Planning, Statistics and Evaluation